Entwined Tellings and the Fragility of the Unique: Relating Narratives of Detention and Survival in Pinochet's Chile. Issue 1 (2nd January 2018) - Bell, Vikki
Abstract: This article considers how we put together stories about the (violent) past, emphasising how stories emerge through our selective attentions that are themselves necessarily dependent on the modes by which the past is sustained, whether those be traces or material supports that sign(post) the past, or through the care and words of human subjects. Taking as its focus the author's experience of chasing stories from the Chacabuco ex-detention centre in the Atacama desert, Chile, the article argues that one's receptivity to stories of 'what happened' requires both passivity to receive and creativity, since nothing – neither art, nor memorials, or even human subjects – truly 'speaks for itself'. As researchers, we facilitate the way stories – often as in this case, shocking, horrific stories, but also humorous, wonderful stories of human kindnesses and sociality – are passed on. Like a game of cat's cradle, we must receive that entangled crystalline past carefully, for we will turn and entwine it such that new relations and connections appear, and others may be lost from sight. Such a process reminds us of an inherent responsibility; the art of allowing related stories to acknowledge the multiple subjects and struggles for which they are told while affirming the fragility of each unique existent.